Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.

Multifaceted core-shell nanoparticles: superparamagnetism and biocompatibility - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Ahir, Manisha; Adhikary, Arghya; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2015)
NicoreAgshell nanoparticles were synthesized by redox transmetallation reaction. Reduction potential match was encouraging to attempt the synthesis of the NicoreAushell system too. However, it could be achieved only after an effective surface modification on the Ni-core. Thorough characterization (UV-Vis spectroscopy, fluorescence spectroscopy, XRD, XPS, FTIR, TEM, and EDX) proved the necessity of surface modification and the success of synthesis of both types of core-shell structures. The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirmed the surface modification of Ni nanoparticles and the interactions involved between the ligands and metals (in the core and/or the shell) at various steps of the synthetic process. Even after the formation of the noble metal shell, the magnetic core was found to retain its superparamagnetic nature. In addition, the Au-shell protected the core from aerial oxidation and decreased toxicity as compared to pristine Ni nanoparticles as observed by MTT assay on normal cells (PBMCs).

Multiple functionalities of Ni nanoparticles embedded in carboxymethyl guar gum polymer: catalytic activity and superparamagnetism - Sardar, Debasmita; Sengupta, Manideepa; Bordoloi, Ankur; Ahmed, Md. A.; Neogi, S. K.; Bandyopadhyay, Sanjoy; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (Applied Surface Science, 2017)
Composites comprising of metallic nanoparticles in polymer matrices have allured significant importance due to multifunctionalities. Here a simple protocol has been described to embed Ni nanoparticles in carboxymethyl guar gum (CMGG) polymer. The composite formation helps in the stabilization of Ni nanoparticles which are otherwise prone towards aerial oxidation. Further the nanoparticles retain their superparamagnetic nature and catalytic capacity. Ni-Polymer composite catalyses the reduction of 4-Nitrophenol to 4-Aminophenol very efficiently in presence of NaBH4, attaining a complete conversion under some experimental conditions. Ni-Polymer composite is well characterized using UV–vis spectroscopy, FTIR, XPS, powder XRD, TGA, SEM and TEM. A detailed magnetic measurement using superconducting quantum interference device-vibrating sample magnetometer (SQUID-VSM) reveals superparamagnetic behaviour of the composite.